1998
DOI: 10.1055/s-2007-1015306
|View full text |Cite
|
Sign up to set email alerts
|

Die Darstellbarkeit der Nierenarterien und Wertigkeit der farbkodierten Duplexsonographie der Nierenarterienstenosen unter Verwendung eines Ultraschall-Signalverstärkers

Abstract: Using an echo-enhancing agent the sensitivity and specificity for detection of relevant renal artery stenosis could only be slightly improved compared to the native examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…Improvements of diagnostic tools such as duplex ultrasound, magnetic resonance tomography angiography, and multislice computed tomography angiography have lead to a more frequent diagnosis of renal artery stenosis during the last decade. [29][30][31][32][33][34][35][36][37][38][39][40][41] The cheapest and easiest to handle diagnostic tool is color duplex ultrasound. However, the accuracy of this method depends on the skill of the physician and the quality of the duplex machine 33 and is furthermore limited by not uniformly defined criteria for the detection of a hemodynamically relevant renal artery stenosis, e.g., a diameter stenosis of at least 70%.…”
Section: Diagnosis Of Renal Artery Stenosismentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements of diagnostic tools such as duplex ultrasound, magnetic resonance tomography angiography, and multislice computed tomography angiography have lead to a more frequent diagnosis of renal artery stenosis during the last decade. [29][30][31][32][33][34][35][36][37][38][39][40][41] The cheapest and easiest to handle diagnostic tool is color duplex ultrasound. However, the accuracy of this method depends on the skill of the physician and the quality of the duplex machine 33 and is furthermore limited by not uniformly defined criteria for the detection of a hemodynamically relevant renal artery stenosis, e.g., a diameter stenosis of at least 70%.…”
Section: Diagnosis Of Renal Artery Stenosismentioning
confidence: 99%
“…However, the accuracy of this method depends on the skill of the physician and the quality of the duplex machine 33 and is furthermore limited by not uniformly defined criteria for the detection of a hemodynamically relevant renal artery stenosis, e.g., a diameter stenosis of at least 70%. [32][33][34][35][36][37][38][39][40][41] The most specific parameter to detect a renal artery stenosis of at least 70% is a side difference of the intrarenal resistance index according to Pourcelot of at least 0.05 with a specificity of up to 100%. 32,35,39 It has been shown that serial duplex ultrasound examination during follow-up after primarily successful stent angioplasty of renal artery stenosis is able to detect restenosis with a high accuracy.…”
Section: Diagnosis Of Renal Artery Stenosismentioning
confidence: 99%
“…Dies widerspricht nur vordergründig den guten Spezifitätswerten anderer Autoren für eine erhöhte systolische Spitzenflussgeschwindigkeit bzw. einen RAQ > 3,0 -3,5 zur Erfassung einer NAST, da sich fast alle Spezifitätsberech-nungen auf angiographisch 50 % -60 %ige NAST bezogen, wodurch hohe Spezifitätswerte zwischen 73 % und 97 % erzielt werden konnten [5,6,8,15,16,19,22,23,52]. Da unseres Erachtens nur NAST ≥ 70 % interventionsbedürftig sind [29,30,43,49,50] -entsprechend dem Vorgehen in der interventionellen Kardiologie -, ist die alleinige Bestimmung der Spitzenflussgeschwindigkeit bzw.…”
Section: Diskussionunclassified
“…Außerdem bezogen sich die meisten Studien zur Validierung der FDS in der Regel auf angiographisch 50 bis 60 %ige NAST [5,6,8,13,16,19,22,23], was aus präinterventio-neller Sicht wenig hilfreich ist, da nach experimentellen Daten [43,49,50] erst Stenosen über 70 % hämodynamisch relevant sind und somit erst dann eine Interventionsindikation besteht [24,25,43]. Wir untersuchten deshalb die Darstellbarkeit der Nierenarterien mittels FDS und die Wertigkeit der am weitesten verbreiteten und einfach zu berechnenden Stenosekriterien RAQ > 3,5 und dRI > 0,05 bzgl.…”
Section: Introductionunclassified
“…[62,63], sind schwer darzustellen [64]. Selbst unter Anwendung von echoverstärkendem Kontrastmittel (Levovist ® ), das eine bessere und leichtere Darstellung der Nierenarterien ermöglicht [65,66], ließ sich von 10 akzessorischen Nierenarterien nur eine nachweisen [67].…”
Section: Screening Und Diagnostische Verfahren Der Nierenarterienstenoseunclassified